Pemanfaatan Pengaruh Subsitusi Semen Menggunakan Abu Batang Jagung (Zea Mays) dan Penambahan Serbuk Cangkang Bekicot (ACHATINA FULICA) Terhadap Kuat Tekan Beton - Dian Ismawan; Agyanata Tua Munthe (Universitas Islam Raden Rahmat, Malang, 2025)
As the height of a structure supported by concrete increases, it demands a higher quality of concrete. However, increasing the use of concrete structures makes the materials that compose the concrete more expensive. In this study, corn stalk ash, which contains silica and has pozzolanic properties, was used to partially replace cement. Meanwhile, powdered snail shell can be assumed to act as a filler to fill the voids between aggregate particles. The study was conducted by replacing 7% of the cement weight with corn stalk ash and adding varying amounts of snail shell powder at 0.3%, 0.5%, 0.7%, and 0.9% of the cement content in the concrete mix for ages of 7 days, 14 days, and 28 days. The goal was to determine its effect on the concrete's density, compressive strength, and water absorption.The results of the study concluded that substituting 7% corn stalk ash and 0.3% snail shell powder after 28 days could increase compressive strength by +10.8%, reduce the density by -2.8%, indicating that the concrete becomes lighter, and reduce water absorption by -0.4%, indicating that the concrete becomes denser, which is beneficial for reinforced concrete as it protects the reinforcement from water and harmful substances. However, this substitution and addition led to a decrease in the slump value, affecting workability and making the concrete more difficult to mold.